(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2024)
The scientific paper is devoted to the problems of legal regulations of service in the USSR militia in the 20s of the 20th century. Legislative and by-laws adopted by the authorities of the Ukrainian SSR during the period under study were used. Some archival documents containing orders of the militia authorities regulating the service were introduced into scientific circulation. During the study period the distinct aspects of service in the Ukrainian SSR militia were identified. It was determined that in the 1920s, educational, political, and health criteria were established for Ukrainian SSR militia service candidates. The procedure for promotion and conditions of service career were established by the Rules of Service in the militia, which were approved by the NKVD of the USSR. The working hours and dismissal conditions of militia officers were regulated by departmental by-laws of the NKVD of the USSR and the collective agreement based on labor legislation. Attention was paid to the 1926 Regulation on the Militia, which stated the application of labor law standards to militia officers with specific exceptions outlined in the legislative act. It was determined that legal protection for militia officers during their duties was governed by the Criminal Codes of 1922 and 1927, along with the norms of the Administrative Code of 1927. The researcher believes that the 1926 Militia Regulation’s provisions, which extended labor law norms to militia officers, are beneficial for updating the current legislation governing police service. It is suggested to consider the possibility of legal regulations of police service based on labor law norms with certain exceptions provided for in the legislation.